2015
DOI: 10.1002/cjce.22322
|View full text |Cite
|
Sign up to set email alerts
|

Review on catalysis related research at CanmetENERGY

Abstract: Canada's oil sands and heavy oil represent a major North American energy source. However, many technological, economic, and environmental challenges must be overcome in order to improve the effectiveness and efficiency required for converting these unconventional oils into clean and high‐quality transportation fuels that meet the ever‐increasing social licence associated with these energy resources. In oil sands bitumen and heavy oil upgrading, and petroleum refining, over 70 % of the processes involve catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the difference in activity between Ni–Mo/AC and Ni/AC catalysts was not primarily due to particle size at 250°C. The critical factor causing Ni–Mo/AC catalysts to be more active at low temperatures may be the electron transfer from MoO 3 to nickel metal 76–78 . Several studies have shown that the process of electron transfer from MoO 3 to metallic nickel (Ni) is the main cause of activity enhancement of Ni–Mo catalysts, especially when used with AC at low temperatures 79–81 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the difference in activity between Ni–Mo/AC and Ni/AC catalysts was not primarily due to particle size at 250°C. The critical factor causing Ni–Mo/AC catalysts to be more active at low temperatures may be the electron transfer from MoO 3 to nickel metal 76–78 . Several studies have shown that the process of electron transfer from MoO 3 to metallic nickel (Ni) is the main cause of activity enhancement of Ni–Mo catalysts, especially when used with AC at low temperatures 79–81 .…”
Section: Resultsmentioning
confidence: 99%
“…The critical factor causing Ni-Mo/AC catalysts to be more active at low temperatures may be the electron transfer from MoO 3 to nickel metal. [76][77][78] Several studies have shown that the process of electron transfer from MoO 3 to metallic nickel (Ni) is the main cause of activity enhancement of Ni-Mo catalysts, especially when used with AC at low temperatures. [79][80][81] The catalyst is activated by this electron transfer mechanism, which increases its efficiency in facilitating a number of chemical reactions, especially hydrogenation and removal of sulfur compounds.…”
Section: Catalyst Activity Influence Of Mo Contentmentioning
confidence: 99%
“…To avoid sulphur poisoning noble metals should be used in environments containing below 10 mgS/g [23]. Generally, Pd stands out among several noble metals for efficiency in hydrocracking (HC) and hydrodesulpharisation (HDS) [87].…”
Section: Supports In Surface Upgradingmentioning
confidence: 99%
“…In particular, catalysts, which are the high dispersion of active sites and the optimization of acid site loading on the surface of the support, should be properly characterized according to the reaction environment [17]. Thus, nickel [18] and molybdate [19] supported on ultra-stable Y zeolite (Ni-Mo/USY zeolite) catalysts have been widely used in HDT reactions [20][21][22][23]. Dien Li et al studied NiMo catalysts that were synthesized using various zeolite types such as NaY, USY, H-mordenite, and ZSM-5.…”
Section: Introductionmentioning
confidence: 99%